Control Structure for Single-Phase Stand-Alone Wind-Based Energy Sources - Barote, L.; Marinescu, C.; Cirstea, M. N. (IEEE transactions on industrial electronics (1982), 2013)
This paper is analyzing the operation of a stand-alone wind turbine system with variable-speed permanent-magnet synchronous generator (PMSG) and a system for storing energy during wind speed and load variations. Energy storage devices are required for power balance and power quality in stand-alone wind energy systems. Initially, the holistic model of the entire system is achieved, including the PMSG, the boost converter, and the storage system. The power absorbed by the connected loads can be effectively delivered and supplied by the proposed wind turbine and energy storage systems, subject to an appropriate control method. The main purpose is to supply 230-V/50-Hz domestic appliances through a single-phase inverter. The simulation results, validated by experimental testing, show a good prediction of the electrical parameter waveforms. The control system is implemented on a dSPACE DS1103 real-time board. Furthermore, the results confirm the stability of the supply.